Risk Factors for Violent Dissident Republican Incidents in Belfast: A Comparison of Bombings and Bomb Hoaxes - Marchment, Zoe (Journal of quantitative criminology, 2020)
To identify risk factors for bombings and bomb hoaxes committed by dissident Republicans in Belfast, Northern Ireland.